2021
DOI: 10.3390/polym13162813
|View full text |Cite
|
Sign up to set email alerts
|

Study of Different Chitosan/Sodium Carboxymethyl Cellulose Proportions in the Development of Polyelectrolyte Complexes for the Sustained Release of Clarithromycin from Matrix Tablets

Abstract: This study investigated the combination of different proportions of cationic chitosan and anionic carboxymethyl cellulose (CMC) for the development of polyelectrolyte complexes to be used as a carrier in a sustained-release system. Analysis via scanning electron microscopy (SEM) Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and powder X-ray diffraction (PXRD) confirmed ionic interactions occur between the chitosan and carboxymethyl cellulose chains, which increases dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…CMC derived from natural materials can hold much water in its structure and be used as a slow-release fertilizer [ 85 ]. Studies have shown that hydrogels prepared by cross-linking with a natural polymer show good biodegradability and mild and controllable reaction conditions, indicating that this is the most ideal method for the synthesis of CMC gels [ 84 , 86 , 87 , 88 ]. The research showed that adding fiber improved the tensile strength of CMC-sodium alginate-glycerol composite films [ 89 ].…”
Section: Cmc Applications In Agriculturementioning
confidence: 99%
“…CMC derived from natural materials can hold much water in its structure and be used as a slow-release fertilizer [ 85 ]. Studies have shown that hydrogels prepared by cross-linking with a natural polymer show good biodegradability and mild and controllable reaction conditions, indicating that this is the most ideal method for the synthesis of CMC gels [ 84 , 86 , 87 , 88 ]. The research showed that adding fiber improved the tensile strength of CMC-sodium alginate-glycerol composite films [ 89 ].…”
Section: Cmc Applications In Agriculturementioning
confidence: 99%
“…At present, the use of environmentally friendly natural polymers is one of the main directions in the pursuit of a modern society. The CMC gels obtained by co-polymerising two types of natural polymers and using biodegradable additives have good biodegradability and are receiving unprecedented attention as a new type of medicinal material [ 39 ].…”
Section: Preparation Of Carboxymethyl Cellulose Hydrogelsmentioning
confidence: 99%
“…CMC is usually an anionic polymer compound prepared by the reaction of natural cellulose with caustic soda and monochloroacetic acid, with molecular weight ranging from tens of millions to millions. Moreover, CMC is a water-soluble polymer with a high viscosity that can improve and sustain soil structure while also increasing cohesion between soil particles [ 10 , 11 ]. Many academics have used it to improve soil structure and water retention performance because of its wide availability, nontoxicity, and easy degradation by microorganisms in the soil [ 12 ].…”
Section: Introductionmentioning
confidence: 99%